Existence and uniqueness of fixed point for Meir‐Keeler type contractive condition in Menger spaces. Issue 2 (3rd December 2020) - Gupta, Vishal; Khan, Mohammad S.; Singh, Balbir; Kumar, Sanjay
Abstract: In this paper, we prove some general common fixed point theorems using generalized contractive condition of Meir‐Keeler type for two pairs of weakly compatible self‐mappings in Menger spaces. Some suitable examples are also given to support our theorems.